A (Re)view of the Philosophical Foundations of Strategic Management - Rabetino, Rodrigo; Kohtamäki, Marko; Federico, Juan S. (Wiley, 2020)
This paper aims to review how different approaches to social inquiry (e.g. positivist, postpositivist, interpretive, postmodernist and critical theory) have been used in strategy research and how these main paradigms engage with strategy. In a fragmented domain, debates typically match paradigms to schools of thought and use the paradigm concept, sometimes even promiscuously, to examine the underlying premises of different theories. Thus, scholars tend to overlook the debate on philosophical meta‐theoretical assumptions (ontological, epistemological and methodological) and prefer onto‐epistemological approaches that are considered to be ‘normal science’, which underestimate the contributions of certain less traditional streams of research. This review offers a fresh view of the philosophical foundations of the strategic literature by combining author co‐citation and content analysis of a sample of academic sources and analyses both the meta‐theoretical assumptions and the basic paradigmatic assumptions for central constructs that strategy researchers attach to their frameworks (e.g. strategy, environment, firm and strategist). This endeavour enables scholars who work in a multidisciplinary field to gain a better understanding of the philosophical beliefs, principles and conventions held by different research communities and theoretical approaches. Exposing the underlying assumptions, as is done in this study, is a key step in theory development. Hence, this review can help researchers, young scholars and doctoral students navigate a confusing research landscape, problematize the existing literature and set new research questions.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|